Possible Usefulness of Gadolinium-Enhanced Brain MRI for Evaluating Risk of Perioperative Hemorrhage: A Case of Infective Endocarditis. (13th February 2014) - Koeda, Chikahiko; Tashiro, Atsushi; Takahashi, Tomohiro; Niiyama, Masanobu; Sakamoto, Ryohei; Kimura, Takumi; Morino, Yoshihiro; Terui, Katsutoshi; Tanaka, Ryoichi; Yoshioka, Kunihiro; Kin, Hajime; Okabayashi, Hitoshi; et al.
Abstract : A 59-year-old woman visited a local hospital for fever and was diagnosed as having infective endocarditis (IE) on the basis of blood cultures and transthoracic echocardiography. Based on clinical episodes of subarachnoid hemorrhage after admission, it was judged that she was not a good candidate for urgent open heart surgery, and it was decided to treat her with conservative medical therapy for the acute phase. We explored the optimum timing for surgery by employing gadolinium (Gd) contrast medium-enhanced magnetic resonance imaging (MRI) T2* weighted image (black dots) due to her high risk of perioperative cerebral hemorrhage. After the disappearance of the contrast media enhancement effect around the black dots, open heart surgery was performed successfully on the 103rd hospitalization day. The patient was discharged 22 days after the surgery with no clinical complications. This case suggests that disappearance of the contrast media enhancement effect around the black dots may be a useful marker for optimal timing of surgery to minimize the risk of perioperative cerebral hemorrhage in patients with IE. Learning Objective . The MRI T2* weighted images including those with Gd contrast medium enhancement effect may be useful for evaluating the risk of perioperative intracranial hemorrhage in IE.